Pengaruh harga, kualitas produk dan citra merek (brand image) terhadap keputusan pembelian mobil toyota kijang innova di samarinda - Irmalisa Irmalisa; Suharno Suharno; J. Kuleh (Faculty of Economics and Business Mulawarman University, 2016)
The purpose of this research was to analyze the factors that have influences toward consumers in the making of purchasing decision. The independent variables of this research consist of Price (X1), Product Quality (X2) and Brand Image (X3). The dependent variable is the car purchasing decisions of Toyota Kijang Innova in Samarinda. The sample used in this research consist of 50 respondents that chosen by Accidential Sampling technique. This research employs multiple regressions. The result of multiple regression is as follows Y = 0,240 + 0,128X1 + 0,331X2 + 0,486X3. Based on the F test and t test, the results obtained that the variable price, product quality and brand image has a positive and significant impacton purchasing decisions. In this research obtained the coefficient of determination (R2) as big as 0,797 which means that the model coefficient of determination is good. This indicates that 79,70% of consumer car purchasing decisions of Toyota Kijang Innova in Samarinda influenced by the variation of the three independent variables are the price, product quality and brand image. While the remaining 20,30% is influenced by other variables that not investigated.Keyword: Price, Product Quality, Brand Image, Purchasing Decisions